Microbes Promote Amino Acid Harvest to Rescue Undernutrition in Drosophila - Ryuichi Yamada; Sonali A. Deshpande; Kimberley D. Bruce; Elizabeth M. Mak; William W. Ja (Cell Reports, 2015)
Microbes play an important role in the pathogenesis of nutritional disorders such as protein-specific malnutrition. However, the precise contribution of microbes to host energy balance during undernutrition is unclear. Here, we show that Issatchenkia orientalis, a fungal microbe isolated from field-caught Drosophila melanogaster, promotes amino acid harvest to rescue the lifespan of undernourished flies. Using radioisotope-labeled dietary components (amino acids, nucleotides, and sucrose) to quantify nutrient transfer from food to microbe to fly, we demonstrate that I. orientalis extracts amino acids directly from nutrient-poor diets and increases protein flux to the fly. This microbial association restores body mass, protein, glycerol, and ATP levels and phenocopies the metabolic profile of adequately fed flies. Our study uncovers amino acid harvest as a fundamental mechanism linking microbial and host metabolism, and highlights Drosophila as a platform for quantitative studies of host-microbe relationships.